Penerapan Program Pengendalian Internal terhadap Biaya Dibayar Dimuka oleh Kap XYZ - Aqil Siraj; Fawwaz Ahmad Kazhimi; Affandi Nur Sidiq; Muhammad Fanar Pamungkas Al Jogja; Ridwan Zulpi Agha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Internal control plays a crucial role in ensuring the reliability of financial reporting and the effectiveness of a company’s operations. One account that requires special attention is prepaid expenses, as its recognition and amortization may lead to misstatements if not properly executed. This study aims to analyze the implementation of internal control over prepaid expense accounts from the perspective of external auditors at Public Accounting Firm XYZ. The research employs a qualitative descriptive method through semi-structured interviews with auditors and examination of supporting documents related to the internal control system. The results indicate that internal control has been implemented through payment authorization procedures, verification of supporting documents, and testing of amortization allocations. However, weaknesses remain, including limited staff understanding of expense allocation policies and inadequate segregation of duties, which increase the risk of material misstatement. The findings highlight the importance of enhancing staff competence, establishing consistent amortization policies, and utilizing technology-based accounting systems to strengthen the effectiveness of internal controls and the reliability of financial reporting.